Prevention of Corruption in Local Self-Government Bodies: Legal Regulation And Foreign Experience - Anton Borysenko; Halyna Tatarenko; Oksana Brusakova; Alla Pyshna; Nataliia Bilak (Magister of Law, Faculty of Law, University of Mataram, 2023)
The article focuses on the negative impact of corruption on the efficiency of the state, the reduction of the governability of the state, and the deterioration of the organization of public life even in the conditions of war in Ukraine. Prevention of corruption risks in local self-government bodies should be implemented by authorities exclusively at the level of a legislative act, necessarily in compliance with the principle of the rule of law and the corresponding guarantees of security in a certain state. The article analyzes in detail the legislation of Ukraine (administrative and criminal legal frameworks) regarding the prevention of corruption risks in local self-government bodies. It was concluded that the strengthening of responsibility for corruption in the conditions of martial law in Ukraine is fully justified, as it is aimed at preventing the